Sutureless technique combined with vertical vein incision and pulmonary veins unroofed for correction of infracardiac total anomalous pulmonary venous connection - Bing, Zhen; Chen, Rui; Xing, Quansheng; Xing, Pengchao; Lv, Bei (Frontiers in Pediatrics, 2023)
Objective We report a surgical method (sutureless technique), combined with vertical vein incision and pulmonary veins unroofed (semisutureless technique), to correct infracardiac total anomalous pulmonary venous connection (TAPVC). Materials and methods The clinical characteristics of 21 patients, who were diagnosed with infracardiac TAPVS between February 2017 and March 2022, were retrospectively analyzed. These patients were divided into three groups according to different surgical methods: conventional surgery group, sutureless technique group, and semisutureless technique group. The conventional surgery group enrolled five patients with a median age of 16 days (interquartile range, 9–27 days) and a median weight of 3.25 kg (interquartile range, 3.1–3.42 kg). In this group, no preoperative pulmonary vein obstruction (PVO), preoperative ventilator support, or emergency surgery were reported. The sutureless technique group enrolled seven patients with a median age of 12 days (interquartile range, 5–16 days) and a median weight of 3.04 kg (interquartile range, 2.76–3.20 kg). In this group, two patients with preoperative PVO, four patients with preoperative ventilator support, and seven patients requiring emergency operation were found. The semisutureless technique group enrolled nine patients with a median age of 14 days (interquartile range, 7–24 days) and a median weight of 3.22 kg (interquartile range, 3.15–3.50 kg). In this group, four patients with preoperative PVO, two patients with preoperative ventilator support, and seven patients requiring emergency operation were noted. Results In the conventional surgery group, two patients with postoperative supraventricular tachycardia, one patient with postoperative low cardiac output syndrome, one patient with PVO, and no case of postoperative death were reported. In the sutureless technique group, two patients with postoperative low cardiac output syndrome, one patient with postoperative supraventricular tachycardia, one patient with postoperative PVO, and no postoperative deaths were determined. In the semisutureless technique group, three patients had low cardiac output syndrome, two patients had supraventricular tachycardia after the operation, and one patient, who had been admitted to the hospital after cardiopulmonary resuscitation in the emergency room, died early after the operation. No case of death or PVO was noted after the operation. Conclusion The semisutureless technique has positive effects. This surgery method can enlarge the anastomotic stoma, increase the volume of the left atrium, reduce the tension of the anastomotic stoma, fix the pulmonary vein to avoid distortion, and prevent postoperative hemorrhage.